Carbon footprint assessment and mitigation options of dairy under Chinese conditions - Hongmin, Dong (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2019)
"Carbon footprint assessment and mitigation options of dairy under Chinese conditions," presented by DONG Hongmin (CAAS) at the CCAFS project meeting with CAAS, CAU & WUR in Beijing, January 15th 2019.